2015
DOI: 10.1016/j.tim.2015.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Towards an HIV-1 cure: measuring the latent reservoir

Abstract: The latent reservoir of HIV-1 in resting memory CD4+ T cells serves as a major barrier to curing HIV-1 infection. While many PCR- and culture-based assays have been used to measure the size of the latent reservoir, correlation between results of different assays is poor and recent studies indicate that no available assay provides an accurate measurement of reservoir size. The discrepancies between assays are a hurdle to clinical trials that aim to measure the efficacy of HIV-1 eradication strategies. Here we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
203
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(211 citation statements)
references
References 111 publications
7
203
0
1
Order By: Relevance
“…S2), which is consistent with other reports [5,6,10,13]. A small proportion of sequences had stop codons not obviously due to G-to-A hypermutation (average 3%, range 0-12%) .…”
Section: Hypermutated Sequences Are Frequent In Hiv-1 Reservoirssupporting
confidence: 91%
See 2 more Smart Citations
“…S2), which is consistent with other reports [5,6,10,13]. A small proportion of sequences had stop codons not obviously due to G-to-A hypermutation (average 3%, range 0-12%) .…”
Section: Hypermutated Sequences Are Frequent In Hiv-1 Reservoirssupporting
confidence: 91%
“…The quantitative virus outgrowth assay (QVOA) represents the "gold standard" [4][5][6], but this assay underestimates the true size of the functional reservoir due to incomplete induction by PHA stimulation. Ho et al [7] showed that the functional HIV-1 reservoir may be 60-fold larger than originally estimated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These therapies are not curative, as latent, transcriptionally silent virus can spontaneously reactivate from sanctuaries and rapidly rekindle viral infection after withdrawal of therapy (1)(2)(3). Therefore, the molecular mechanisms of the activation and suppression of HIV transcription are of great interest.…”
mentioning
confidence: 99%
“…Tat is a small protein, typically found in a full-length form of ϳ101 amino acids (aa) 3 or as a splice variant (72 aa) encoded only by the first exon of the tat open reading frame. Both isoforms efficiently transactivate the HIV promoter in the 5Ј long terminal repeat (LTR).…”
mentioning
confidence: 99%